Studi Eksperimen Matriks Dan Fiber Komposit Sebagai Material Bodi Remote Control Boat - Budiono, Andik; Kusumaningrum, Ira; Usman, Mualifi (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
This research aims to evaluate the performance of composite materials made from woven cloth, fiberglass and banana fronds in making Remote Control Boat bodies. As the need for fast ships and performance efficiency increases, selecting light and tough materials becomes the main key in ship hull design. The research was carried out experimentally with a toughness testing method (impact test) using the ASTM D256 standard. The independent variables used include fiber type (woven cloth, fiberglass, and banana fronds), resin type (epoxy and polyester) with a 3×2×3 factorial design and three repetitions. It is hoped that this research can contribute to the development of alternative materials in the small-scale shipping industry and become a reference in the use of natural fibers as composite reinforcing materials.